Innovations in Agricultural Inputs and Services Markets in India: A Pathway to Sustainable Agricultural Growth - Kumar, Shalander (2025)
The evolution and adoption of innovations in agricultural input and services markets (AI-SM) have been among the primary drivers of agricultural growth and development. Facing increasing challenges, including climate change, market volatility, global supply chain disruptions, and unsustainable farming practices alongside emerging opportunities from digital technology advances, innovation in AI-SM has become essential for achieving sustainable farming and food systems. This paper provides a comprehensive analysis of AI-SM and related innovations, emphasizing their critical role in promoting sustainable agriculture and food systems. It examines the mechanisms, institutions, and service provisions that can facilitate access to agri-input technologies, including advances in seeds, machinery, fertilizers, bio-inputs, livestock services, climate services, and data-driven digital tools and innovations, to enhance productivity, income, and environmental sustainability. The paper also analyses smallholder farmers' challenges in accessing AI-SM through current public and private delivery systems, identifying possible strategies for overcoming the barriers. It also explores policy pathways to leverage emerging digital technologies to improve farmers' access to high-quality agri-inputs and services, thereby supporting current and future farming systems focused on increasing farm incomes, resilience, and long-term sustainability. This paper seeks to promote inclusive and sustainable farming and food systems that can meet global food demands while conserving natural resources by offering practical insights for policymakers, investors, and agricultural practitioners.